Development of Facilitated Participatory Spatial Information System for Selected Urban Management Services - Simeon, Ozuomba; Constance, Kalu; Ekanem, Akpasam Joseph (Review of Computer Engineering Research, 2018)
In this paper, the development of a web based spatial information system for selected urban management services in Akwa Ibom state is presented. The selected urban management services include; disaster management, waste management, land administration and land transportation information hub. Participatory evolutionary software development methodology was used in the system development and the system was implemented using Hyper Text Markup Language (HTML) for the web interface, PHP Hypertext preprocessor (PHP) for the server side scripting , MySQL for the database, Google map API (Application Programming Interface) for the maps and Apache as the web server. The web application was hosted locally using WAMP server and tested with some dataset obtained in the case study area. Relevant screenshots of the webpages are also presented. The web application presented in this paper can be used to facilitate participatory urban service in any given city or state.